The Value and Inheritance Strategies of Tai Chi in the New Era - Wang, Weiyan; Li, Zhou (The Journal of the International Society of Chinese Health Practices, 2024)
Abstract: Taijiquan is an important part of Chinese traditional culture, which has a long history and rich cultural connotation. Under the background of the new era, Taijiquan has the value of shaping the national image of "harmonious China", promoting global cultural exchange and mutual learning, promoting the development of global health preservation, the expression medium of free spirit, and promoting the art of time and space. This paper uses the literature data method and the expert interview method to explore the contemporary value of Taijiquan and the path of educational inheritance. Taijiquan has a profound impact on body cognition, body technology and cultural symbols, and also plays a positive role in cross-cultural communication and identity. As a unique body practice and cultural heritage, Tai Chi has attracted people from all over the world. This paper focuses on the application value of Tai Chi in contemporary society and its implementation path in educational inheritance, in order to provide theoretical support and practical guidance for the inheritance and development of Tai Chi. The philosophical thinking and unique body language of Tai Chi have had profound effects on a global scale. Taijiquan integrates Taoism, Confucianism and military strategists, with profound cultural connotation and unique martial arts style. As an intangible cultural heritage, maintaining and inheriting Taijiquan is of great significance for maintaining and carrying forward the cultural tradition of the Chinese nation and displaying the diversity of Chinese culture. At the same time, Taijiquan is not only one of the representative types of martial arts, but also a cultural phenomenon with body perception and expression as the core. In the context of the new era, the application value of Taijiquan is more extensive. First of all, Taijiquan can shape the national image of "harmonious China", and help the promotion and dissemination of the national image through the establishment of multi-dimensional and three-dimensional publicity. Secondly, Taijiquan can promote global cultural exchanges and mutual learning, show the unique charm of Chinese culture through cross-cultural exchanges and international competitions, and promote exchanges and understanding among different cultures. In addition, Taijiquan can also promote the development of global health preservation. As a form of healthy exercise, Taijiquan has a positive role in the improvement of physical function and mental health, and can contribute to the cause of global health. Taijiquan can also act as a medium of free spirit, conveying thoughts, emotions and values through the use and expression of body language. In addition, Taijiquan can also promote the value of The Times with time and space art, through the combination and innovation with dance, painting and other arts, to show a more colorful art forms and expressive force. In order to better promote and popularize Taijiquan, this paper puts forward the following strategies: First, establish a multi-dimensional and three-dimensional publicity mechanism to improve the public's awareness and attention to Taijiquan. Through media publicity, cultural exchange activities, sports events and other forms, more people can understand and understand the cultural connotation and application value of Taijiquan. Secondly, innovate teaching methods and methods to improve the quality and effect of Tai Chi education. Modern technology and diversified teaching methods, such as online teaching and interactive teaching, so that more people can learn Taijiquan easily and quickly. Third, deepen the depth of Taijiquan research, and strengthen the transformation and application of scientific research results. It can strengthen exchanges and cooperation with other disciplines, carry out in-depth research, and explore the profound influence and function mechanism of Taijiquan on physical cognition, body technology and cultural symbols. Fourth, establish a social participation mechanism for the inheritance and development of Taijiquan to stimulate the enthusiasm of social forces to participate in the inheritance and development of Taijiquan. It can guide social organizations and groups to participate in the inheritance and development of Tai Chi, strengthen the integrated development with related industries and fields, and promote the prosperity and development of Tai Chi industry. To sum up, Taijiquan, as an important part of Chinese traditional culture, has extensive application value and educational inheritance significance. Under the context of the new era, we should strengthen the research and promotion of Taijiquan, and give full play to its positive role in shaping the national image of "harmonious China", promoting global cultural exchanges and mutual learning, and promoting the development of global health preservation. At the same time, we should also strengthen the work of teaching innovation and educational inheritance, provide theoretical support and practical guidance for the inheritance and development of Taijiquan through the implementation of corresponding development strategies, help them to better serve the cause of human health and cultural exchanges, further promote Chinese culture to the world stage and play a greater role.